Effect of canal dryness and flaring on the accuracy of two electronic apex locators - Hamed, Bashdar M; Kaka, Ihsan N (Journal of Baghdad College of Dentistry, 2013)
Background: This in vitro study evaluated the effect of canal dryness and flaring on the accuracy of two electronic apex locators for working length (WL) determination. Materials and methods: Sixty extracted teeth were used, after access opening was done, the occlusal surface was flattened to create stable reference point. The teeth were randomly divided into two equal main groups of flared and unflared group each one of 30 teeth. The flaring was done with Gates Glidden drills. The two main groups were further subdivided into two subgroups: dry canal and wet canal using 5.25% sodium hypochlorite groups, Electronic WL of each sample was determined using both Root ZX and i-Root apex locator. Consequently, histologic WL was determined by shaving the apical 4mm of the root longitudinally and the tip of # 15 K-file was adjusted to the apical constriction under stereomicroscope at a magnification 20X, then the file removed carefully and the length was recorded using digital caliper. The data had been collected from two independent examiners and statistically analyzed using Student's t-test. Results: The results showed differences between flared and unflared canal, wet and dry, Root ZX and i-Root apex locators, however the differences between them were statistically not significant, in which (P ? 0.5) for all situations. Conclusion: dryness of the canal, coronal flaring had little effect on the accuracy of electronic apex locators (EALs).